2017
DOI: 10.1016/j.jhydrol.2017.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Climate and land-use change impact on faecal indicator bacteria in a temperate maritime catchment (the River Conwy, Wales)

Abstract: use change impact on faecal indicator bacteria in a temperate maritime catchment (the River Conwy, Wales),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…The model simulates a range of processes governing microbial transport, growth and die-off, and parameters may be varied at a sub-catchment scale to enable a spatially variable representation of key processes. A full description of the Total Coliform model and applications in England, Wales and Finland are given by Whitehead et al (2016), Bussi et al (2017), and Rankinen et al (2016).…”
Section: Water Quality In the River Systemmentioning
confidence: 99%
“…The model simulates a range of processes governing microbial transport, growth and die-off, and parameters may be varied at a sub-catchment scale to enable a spatially variable representation of key processes. A full description of the Total Coliform model and applications in England, Wales and Finland are given by Whitehead et al (2016), Bussi et al (2017), and Rankinen et al (2016).…”
Section: Water Quality In the River Systemmentioning
confidence: 99%
“…It is a well-mixed, macro-tidal estuary with a tidal range of 4–6 m [ 19 ]. The estuary and nearshore coast is an important area for the cultivation of mussels [ 20 ] and a tourist region with several blue-flag bathing beaches. There are three main WWTPs, more than 15 smaller WWTPs, and 35 combined sewage outfalls that discharge into the river network [ 21 ]; all potential sources of bacterial contamination [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Fairweather et al [23] found high multivariate dispersion among downstream samples as well as overall sample dissimilarity that indicated higher heterogeneity downstream. Bussi et al [24] stated that climate change has no big impact on average river flow and land use change can have a large impact on pathogens.…”
Section: Possibility Of River Watersheed Contaminationmentioning
confidence: 99%